Authentic violence: The changing sameness of 'real' Romani discourse in Dominic Reeve's life story. Issue 2 (November 2016) - Shaw, Martin
Abstract : The article focuses on the discourse of the real or true Romani/traveller in Dominic Reeve's life story, which consists of five autobiographical texts published between 1958 and 2010. Reeve defends various factions of Romanies/travellers from a real/fake dichotomy that partially dominates negotiations of recognition. This discourse changes over time from biological to bio-cultural and then to cultural, but then on to bio-genetic and finally a conflation of bio-genetic and cultural discourse. However, throughout these changes there is a structural sameness that Reeve cannot quite escape, and which casts doubt on whether the discourse actually does change. Ultimately, Reeve attempts to settle on a traveller- gauje divide, but the real/fake discourse re-emerges, thus reproducing the dominant discourse itself. During these negotiations, Reeve communicates with three seemingly competitive views of Romani/traveller identity, and in a sense re-unites them. On a more subjective level, Reeve gradually negotiates a much-desired position of group belonging for himself and this brings the life story into the frame of the bildungsroman.